Integrated nutrient management by using targeted yield approach for rice–blackgram sequence - MOUNIKA, D.; LUTHER, M. MARTIN; SEKHAR, K. CHANDRA; BABU, G. KISHORE; LALITHA, K. JAYA (Journal of Soil and Water Conservation, 2021)
A field experiment was conducted at the Agricultural College farm, Bapatla, during kharif and rabi seasons of 2017-18 and 2018-19. The experiment was conducted with blackgram variety BPT-5204 in a Randomized Block Design with ten treatments and three replications. The maximum grain yield, soil NPK status at post-harvest of rice and gross returns net returns, returns per rupee investment were recorded with soil test based fertilizer recommendation with 10 t ha-1 farm yard manure (FYM) application which was at par with soil test based fertilizer recommendation alone and 7.5 tha-1 targeted yield recommendation along with FYM and recommended dose of fertilizers (RDF) with FYM. Grain yield of rice was significantly higher with soil test based fertilizer recommendation with 10 t ha-1 FYM application which was statistically at par with soil test based fertilizer recommendation alone and 7.5 t ha-1 targeted yield fertilizer recommendation with FYM compared to the rest of the treatments.